2007
DOI: 10.2166/wst.2007.803
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of perfluoroalkyl sulfonates and carboxylates in German drinking water sources compared to other countries

Abstract: Different homologues of C4 to C8 perfluoroalkyl carboxylates (PFCAs) and perfluoroalkyl sulfonates (PFASs) were detected in German surface waters, bank filtrates, artificially recharged groundwaters, and drinking waters. If no point sources are located nearby, the typically measured levels are in the low ng/L range. In the presence of point sources, such as a fluorochemical production site, a leaching agricultural fertilizer contaminated with PFCAs and PFASs, or drained PFC containing fire-fighting foams, much… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 25 publications
2
20
0
Order By: Relevance
“…The average concentrations of fluorochemicals in the Glatt River were higher than values reported in surface waters in Scandinavia (22) and northern Italy (10). PFBS was the most abundant fluorochemical found in the Rhine by two separate studies, Skutlarek et al (8) and Lange et al (25), which was not the case for the Glatt. PFNA, PFOA, PFHpA, and PFHxA concentrations measured at the mouth of the Rhine River were all higher than the concentrations in the Glatt River (11), which indicates that the Glatt River is but one source of fluorochemicals in the Rhine River.…”
Section: Resultsmentioning
confidence: 91%
“…The average concentrations of fluorochemicals in the Glatt River were higher than values reported in surface waters in Scandinavia (22) and northern Italy (10). PFBS was the most abundant fluorochemical found in the Rhine by two separate studies, Skutlarek et al (8) and Lange et al (25), which was not the case for the Glatt. PFNA, PFOA, PFHpA, and PFHxA concentrations measured at the mouth of the Rhine River were all higher than the concentrations in the Glatt River (11), which indicates that the Glatt River is but one source of fluorochemicals in the Rhine River.…”
Section: Resultsmentioning
confidence: 91%
“…In contrast, typical ranges in fluorochemical concentrations are 0.5 – 1,000 ng L −1 for municipal wastewaters (Schultz et al, 2006; Loganathan et al, 2007; Becker et al, 2008; Huset et al, 2008) and 0.1 – 150 ng L −1 for surface waters (Lange et al, 2007; McLachlan et al, 2007; Becker et al, 2008; Huset et al, 2008). Land-application of solid and liquid waste and point sources associated with fluorochemical manufacturing are thought to contribute to higher (1,200–34,000 ng L −1 ) surface water concentrations (Skutlarek et al, 2006; McLachlan et al, 2007; Konwick et al, 2008).…”
Section: Resultsmentioning
confidence: 95%
“…Initially, Saito et al (2004) reported PFOS concentrations in tap water from Japan to fall between 0.1 and 12.0 ng/L. Later studies (Lange et al, 2007;Ericson et al, 2009;Skutlarek et al, 2006;Tanaka et al, 2008) have reported higher concentrations however; up to 58 ng/L and 143 ng/L PFOS in tap water from Spain (Ericson et al, 2009) and Japan respectively. Overall, PFOS is one of the most frequently detected PFASs (together with PFOA) in drinking water, with detection frequencies varying between 40 and 100% in published papers.…”
Section: Drinking Watermentioning
confidence: 97%